Impelementasi Metode Takrir dan Tasmi’ Dalam Meningkatkan Kualitas Hafalan di Asrama Hasbullah Said Denanyar Jombang: studi alquran - Hafid, Abdul; Nasrulloh, Nasrulloh (Pascasarjana IAIN Metro, 2023)
There are many complaints from good friends who are memorizing the Al-Qur'an and those who have memorized the Al-Qur'an. They find it difficult to memorize and recite the Qur'an. This study aims to find out the process of implementing the takrir and tasmi' methods in memorizing the Qur'an, the results achieved in these methods and how they are evaluated in practice. The researcher uses a qualitative descriptive method with a phenomenological approach. Meanwhile, data collection techniques used interview, observation and documentation methods. The results showed: First, the overall process of implementing the takrir method in memorizing the Qur'an at the Hasbullah Said boarding school Denanyar Jombang Islamic Boarding School has been going well, this is based on the fact that the entire process of implementing Al-Qur'an memorization has been carried out using takrir and tasmi' method. Second, the results that have been achieved from the application of the takrir and tasmi' methods are fairly good and successful, the indication is that most of the tahfidz students can memorize half a juz of Al-Qur'an verses per month, which has met the institution's target. As for evaluating the implementation of the takrir method, tiered deliberations will be carried out, namely every 2 or 3 months according to needs, this is done to find out the targets of the pondok that have been achieved and the targets of the pondok which have not been achieved so that to solve them requires periodic deliberations and consistently besides that this deliberation aims to find new ideas for the progress of the Islamic boarding school